ANALISIS FAKTOR-FAKTOR PENGHAMBAT GURU DALAM PEMBELAJARAN MATEMATIKA DI SD INPRES OEBUFU, KOTA KUPANG - Melkianus Ndolu; Wara Sabon Dominikus; Sarah Nurhabibah (Universitas Nusa Cendana, 2022)
Mathematics is a universal science that has an important role in various disciplines and develops the human mind, and underlies the development of modern technology. Therefore, mathematics subjects need to be given to all students from elementary school to high school levels to equip students with the ability to think logically, analytically, systematically, critically, and creatively, and be able to solve the problems they face in everyday life. The purpose of this study was to determine the inhibiting factors of teachers in learning mathematics and the efforts made to overcome the inhibiting factors of teachers in learning mathematics at elementary school Inpres Oebufu, Kupang City. The results of this study indicate that the inhibiting factors for teachers in learning mathematics are the lack of interest and motivation of students in learning, there is insufficient infrastructure and must be made by the teacher, and the family environment and residence that do not support students' interest and motivation to learn. at home. Efforts are being made to overcome the inhibiting factors of teachers in learning mathematics, namely every time the teacher starts a lesson the teacher gives enthusiasm and motivates students to focus on learning, provides stabilization in the study of material, and provides sufficient media.